EFFECT OF SUPPLEMENTATION OF PROBIOTICS AND MULTIENZYMES IN LOW PROTEIN DIET ON THE PERFORMANCE OF JAPANESE QUAILS - Rathi, A D; Kukde, R J; Ramteke, B N; Lanjewar, R D; Patankar , R B (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted to study the effect of probiotics and multienzymes in low protein diet of Japanese quails. One hundred sixty quail chicks were uniformly distributed into four groups viz. T0, T1, T2 and T3. Group T2 was supplemented with probiotics and group T3 was supplemented with multienzymes. There was significant (P<0.01) increase in final live body weight and average weight gain in T3 group . The feed consumption of the T2 and T3 group were significantly (P<0.01) increased than T0 and T1. There was significant improvement in FCR in T2 and T3 group as compared to T0 and T1 group. The nitrogen retention was 67.24, 64.91, 61.0 and 60.0 per cent in T3, T2, T0 and T1 respectively. Dressing percentage was 78.84, 77.96, 74.14 and 71.89 percent in T3, T2, T0 and T1 group respectively. Organoleptic test reveals that supplementation of probiotics and multienzymes did not have any objectionable flavour and taste to meat.